Green Libraries- Sustainable Innovations and Practices: An Overview - Mojjada, Harihararao; Kumar, P Suresh (International Journal of Information Studies, 2025)
Sustainable principles are an integral part of green libraries, encompassing green technology, energy conservation, and environmental considerations. Firms with higher levels of green innovation have a positive impact on green firm performance, as evidenced by energy-saving or waste-reduction practices. These libraries demonstrate how they lower their eco-centric footprint through the use of dynamic renewable energy sources, water conservation systems, and sustainable materials, with a focus on community and resource preservation, aiming to create places that reduce environmental impact and spark a vision of a sustainable future. This paper examines the future of green libraries by exploring emerging trends, innovations, and best sustainability practices. A spontaneous solution is what this is all about, as discussed at the tech talk on ‘Ingenuity, sustainability and the future library’, covering everything from architectural innovations to energy sustainability, from digital transformation to global proposals for policy changes that can inspire every effort to green libraries.